2018
DOI: 10.3389/fpsyg.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Preschool Teachers' Responses to Bullying Scenarios: The Roles of Years of Study and Empathy

Abstract: The present study is aim to examine whether preservice preschool teachers' respond differently to physical, verbal and relational bullying, and how their years of study and trait empathy related their responses. There were 242 preservice teachers in the present study. Empathy was measured with the self-report Interpersonal Reactive Index; the Bullying Attitude Questionnaire was used to assess their perceptions of incident seriousness, their sympathy toward the victim of the bullying, and their possibility to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
(80 reference statements)
0
18
0
2
Order By: Relevance
“…The manifestation of peer victimization in the preschool years is similar to that of school-age children in many ways but differs in others depending on the child’s development of social cognition [21]. Younger students usually tend to resort to physical aggression, possibly because they have not yet developed the required sophistication of verbal or social skills to obtain what they want.…”
Section: Introductionmentioning
confidence: 99%
“…The manifestation of peer victimization in the preschool years is similar to that of school-age children in many ways but differs in others depending on the child’s development of social cognition [21]. Younger students usually tend to resort to physical aggression, possibly because they have not yet developed the required sophistication of verbal or social skills to obtain what they want.…”
Section: Introductionmentioning
confidence: 99%
“…Among the components of empathy, personal distress and fantasy facilitate the overwhelming merging from self to others to feel the others’ feeling, which increases one’s susceptibility to negative emotions and stresses and consequently results in higher risk of stress and mental health problems ( Keaton, 2017 ; Huang et al, 2018 ). Empathic concern and perspective taking are based on the distinction between self and others, protect one from being overwhelmed by others’ emotion, and consequently help in resisting stress and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Experience is also found to be related with empathy. For example, in psychiatrists, subjects with more years of experience had lower empathic concern scores (Santamaría-García et al, 2017); in preservice preschool teachers, years of study is also found to correlate with various dimensions of empathy (Huang et al, 2018). Katz (1972) has emphasized that teaching experience is one of the core variables of preschool teachers' characters.…”
Section: The Role Of Teaching Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Empathy can also influence teachers' attitudes and behaviors toward vulnerable populations and diverse youth in multicultural schooling contexts. Affective empathy in particular seemed to play an important role in special education and general education teachers' positive attitudes toward their students with disabilities (Parchomiuk, 2019) and student–teachers' likelihood of intervening in a bullying scenario (Huang et al, 2018). Both forms of empathy related to increased use of culturally sensitive practices when teaching diverse populations of students (Warren, 2018).…”
Section: Introductionmentioning
confidence: 99%